Physicochemical Properties and Microbial Storage Stability of Tiri Traditional Iranian Flat Bread - Sara Mazidi; Mohammad-Hadi Eskandari; Mehrdad Niakosari; Reza Mostowfizadeh-Ghalamfarsa; Mahboobeh Fazaeli (International Journal of Nutrition Sciences)
Background: Tiri bread is one of the oldest known bread types in the Middle East. It is single layer, unleavened, soft, and flat traditional bread baked at home. Dry bread has a long shelf life if stored appropriately at room temperature, but a fresh bread gets moldy with off-flavor 3-4 days after baking. This study has assessed physicochemical properties and microbial storage stability of Tiri bread as traditional flat bread in Iran.Methods: Twenty samples of fresh home-baked Tiri bread were examined for their physicochemical characteristics and shelf life stability at 4°C and 25°C. Their most common spoiling factors, morphological and molecular attributes were investigated. The breads were assumed unhealthy for consumption when the first sign of mold strains appeared.Results: The thickness (0.4-0.9 mm), water activity (0.82-0.90), moisture content (18.08-24.13%), salt content (1.59-3.24%), pH (5.75-5.95), and total titrable acidity (2.00-2.90 mL;0.1 N NaOH) were determined. The shelf life of fresh Tiri bread was 10 and 4 days at 4°C and 25°C, respectively. The main factors limiting the shelf life of these breads were appearance of mold as well as development of an off-odor. The most common isolated species were Aspergillus niger (31.38%), A. flavus (16.12%), A. tubingensis (15.12%), A. awamori (12.10%), A. ochraceus (10.14%), and Penicilliumcorylophilum (16.26%).Conclusion: As some types of fungi produce harmful toxins which may trigger allergic reactions and can cause harmful infections, it is vital to set out principles concerning safety and health during production and storage of these breads to pay attention to the production and storage conditions of Tiri bread to inhibit mold growth.